2015
DOI: 10.3109/21691401.2015.1052470
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dobutamine on extravascular lung water index, ventilator function, and perfusion parameters in acute respiratory distress syndrome associated with septic shock

Abstract: During the early stage of septic shock-induced ARDS, dobutamine treatment demonstrated a beneficial effect by relieving pulmonary edema in patients, without a negative elevation in preload or hemodynamics, which might account for the improvements in ventilator function and tissue hypoperfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…In our study, the early administration of medication reduced the 28-day mortality, improved the shock reversal rate, shortened the ICU stay, and decreased the duration of mechanical ventilation. Further, a prospective study by Zhou showed that in the early stage of acute respiratory distress syndrome caused by septic shock, dobutamine increased the cardiac output, reduced pulmonary edema in patients and reduced the required dose of norepinephrine ( 24 ). Fink et al confirmed that dobutamine can improve liver function and hepatic microcirculation in septic shock ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the early administration of medication reduced the 28-day mortality, improved the shock reversal rate, shortened the ICU stay, and decreased the duration of mechanical ventilation. Further, a prospective study by Zhou showed that in the early stage of acute respiratory distress syndrome caused by septic shock, dobutamine increased the cardiac output, reduced pulmonary edema in patients and reduced the required dose of norepinephrine ( 24 ). Fink et al confirmed that dobutamine can improve liver function and hepatic microcirculation in septic shock ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Dobutamine (DBT) [1,2-Benzenediol, 4-(2-((3-(4-hydroxyphenyl)-1-methylpropyl)amino)ethyl)-, (±)-] is a beta-1 adrenergic agonist and was first developed as a structural analogue of isoprenaline [20] . DBT revealed that during the early stage of septic shock-induced ARDS, DBT treatment indicated a beneficial effect by relieving pulmonary edema in patients [21] . DBT was also shown to be effective for renal function parameters and it was well tolerated and elicited few side effects, thus, DBT appears to be used safely [22] .…”
Section: Introductionmentioning
confidence: 98%